THE EFFECT OF CONCENTRATION AND LONG MARINATION WITH THE EXTRACT OF BIDARA FRUIT (Ziziphus mauritiana) ON COOKING LOSS, pH, AND ORGANOLEPTICS OF SPENT LAYING HENS MEAT - S., Maryam; Wibawa, A.A.P.P.; Okarini, I.A. (Jurnal Peternakan Tropika; Vol 11 No 3 (2023): Vol. 11 No. 3 Tahun 2023; September - December, 2023)
This study aims to determine the effect of concentration and duration of marinade of bidara fruit ( Ziziphus mauritiana ) in meat marinade and its effect on the characteristics of rejected laying hens. This study used a completely randomized design (CRD) with a two-factor factorial pattern with the first factor being the concentration of bidara fruit extract, namely K1 (25%) and K2 (50%) and the length of marinade namely L1 (1 hour) and L3 (3 hours). The variables observed were cooking loss, pH value, aroma, taste and tenderness. The average cooking loss showed that the K1L3 and K2L1 treatments showed significant results (P<0.05). The results of the study showed that the pH value of the breast meat of rejected laying hens marinated with bidara fruit extract showed that the K1L1 treatment gave the highest average of 5.13 and was higher than K1L3, K2L1 and K2L3, the results were not significantly different (P> 0.05). Subjective tests of aroma, taste and tenderness had no significantly different results (P>0.05). Based on the results of the study, it can be concluded that the effect of concentrations of 25% and 50% with a marinated time of 1 hour and 3 hours, has a significant effect on the cooking loss of laying hens meat producing the best results in K2LI (50% concentration and 1 hour marinade) and KIL3 ( 25% concentration and 3 hours of marinade). Keyword : Marinated, bidara fruit extract, organoleptic